Analysis of the Law Relating to Agency Banking in Uganda - WYCLIFFEE, MUTUNGI (Journal of Ecohumanism, 2025)
Agent banking is a business of providing banking services to the customers of a bank or a financial institution on behalf of that particular bank or financial institution under a valid agency agreement. The parliament of the republic of Uganda passed the Financial Institutions (Amendment) Act, 2016 which provides for agent banking. Agent banking governed by the financial institutions (amendment) act, 2017 has enabled the financial institutions to enter into Digital Financing Space to drive financial inclusion and increase access to financial/banking services to a range of under-served and unbanked population segments. This study aimed at ascertaining the adoption of agency banking system in Uganda looking critically on the analyzing of the legal and institutional frame work of agency banking, its implications with other laws and the challenges facing the development. The major approach taken to achieve the objectives of the study is doctrinal approach that prioritizes the use of statutes, case law, legal text, text books, journals, reports, articles and other pertinent sources that systematically discuss and analyses the various principles of agency banking in Uganda and other jurisdictions. The agency banking system is designed to decongest the banking halls and extend banking services to rural areas where the cost of establishment and maintenance of a bank branch would be a burden to the Financial Institution. Agency banking has been effective in several countries for instance in Kenya, south Africa, Nigeria, brazil, Pakistan, Indonesia among others. Since its launch in 2016, agent baking has seemed a successful channel for improving commercial banks market shares, financial performance, profitability as well as promoting financial inclusion. However, it has faced a number of problems which are legal, technical or operational.